2021
DOI: 10.1186/s13023-021-01743-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural progression of cardiac features and long-term effects of enzyme replacement therapy in Taiwanese patients with mucopolysaccharidosis II

Abstract: Background Cardiac abnormalities have been observed in patients with mucopolysaccharidosis type II (MPS II). The aim of this study was to investigate the cardiac features and natural progression of Taiwanese patients with MPS II, and evaluate the impact of enzyme replacement therapy (ERT) on cardiac structure and function. Methods The medical records and echocardiograms of 48 Taiwanese patients with MPS II (median age, 6.9 years; age range, 0.1–27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…In our study, valve abnormalities were the most commonly observed cardiac manifestation of MPS II. The most common specific manifestations observed were mitral/tricuspid valve regurgitation (71.9%), aortic/pulmonary valve regurgitation (36.8%), in agreement with the report by Lin et al (2021). Therefore, echocardiography should be checked regularly (Scarpa et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, valve abnormalities were the most commonly observed cardiac manifestation of MPS II. The most common specific manifestations observed were mitral/tricuspid valve regurgitation (71.9%), aortic/pulmonary valve regurgitation (36.8%), in agreement with the report by Lin et al (2021). Therefore, echocardiography should be checked regularly (Scarpa et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Muscle-specific downregulation of D-idua led to death at pupal stage suggesting that D-idua is a key player in muscle development and/or maintenance. This possibly reminds of musculoskeletal difficulties, as well as the important cardiac involvement, typical of MPS I patients [ 57 , 58 , 59 ]. Our analysis further suggested a role of D-idua in CNS development and functionality.…”
Section: Discussionmentioning
confidence: 98%
“…The natural history of MPS has shown that cardiac abnormalities in these individuals worsen with age. It has been demonstrated that initiating ERT in these patients can help to stabilize and even reverse cardiomyopathy [ 24 , 25 , 26 ]. As a result, early discovery and initiation of treatment are crucial for improved outcomes, which can be accomplished by neonatal screening.…”
Section: Discussionmentioning
confidence: 99%